RETRACTED: Overview of modern methods of treatment and disposal of sewage sludge - Jumasheva Kamshat; Syrlybekkyzy Samal; Serikbayeva Akmaral; Suleimenova Botakoz; Altybayeva Zhansaule (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001